To compare the effect of plyometric training and core stability training on agility in badminton players - Agarwal, N.; Moharkar, A. C.; Golhar, S. (International Journal of Yoga, Physiotherapy and Physical Education, 2019)
The purpose of the study was to compare the effect of plyometric training and core stability training on agility in badminton players by the end of 6 weeks. 40 participants (including both male and female subjects) ranging from 16-18 years of age, they were selected on the basis of T-test for agility randomly with a scoring ranging from fair-12.8-14.0s. The subjects were evaluated before and after 6 weeks. Each group was given training 3 times a week. Statistical analysis of the data was done using paired t test within group and unpaired t test between groups, there was statistical difference within pre and post analysis of plyometric training (p value <0.0001) and pre and post analysis of core stability exercises (p value <0.0001), but there was no significant difference seen when comparison was done between the groups (p value 0.2030). Based on the finding of the study both plyometric training and core stability training help in improving agility in badminton players.